(untitled) (Polish Yearbook of International Law, 2016)
One of the most significant changes in modern arbitration rules is the adoption of emergency arbitrator proceedings. These proceedings were introduced in order to provide a party in need of urgent interim measures before the constitution of an arbitral tribunal with an additional option besides going to state courts. In emergency arbitrator procedures such a party may seize an emergency arbitrator to grant the requested urgent relief. This article provides the Polish perspective on the effectiveness of emergency arbitrator proceedings, given that the Polish law is silent on the institution of emergency arbitrator and the possible recognition and enforcement of the decisions of an emergency arbitrator. The article analyses the Polish regulations on interim measures, together with their enforcement, by comparing the relationship, similarities and divergences between an arbitral tribunal, a state court, and an emergency arbitrator. This brings us to the conclusion that the existing legal framework as to the enforcement of interim measures issued by an arbitral tribunal provides a solid foundation for drawing an analogy to the recognition and enforcement of such orders granted by an emergency arbitrator. Thus, the provisions on enforcement of arbitral tribunal’s orders per analogiam allow for the recognition and enforcement of emergency arbitrators’ decisions on interim measures in Poland.